Zmysły i edukacja. O roli doświadczenia, wiedzy oraz selekcji (refleksja filozoficzna w edukacji) - Futyma , Sławomir (Studia Edukacyjne, 2017)
Sensory experience leads to the initiation of a complex process of thinking about the world. The result of this process are the images of what surrounds us. We definethis action as education. Because looking at the world from the perspective of sensual experience is the potential ability of every human being (Hannah Arendt), education becomes a tool enabling the simulation of the existing world and the one that may appear in the future. About who we are and where we are, who we will decide, the quality of the senses. The quality of the senses translates into the value of the cognitive process. The consequence of the quality of the cognitive process is the collection of information and knowledge. This sensual logic inscribes the action that classifiesus people according to predisposition or ava-ilable information that results from the quality of sensual functioning. As Leonardo da Vinci saw it: “Experience, the intermediary between creative nature and the human race, teaches what nature uses among mortals, that before the necessity of necessity one cannot act differently than reason, his teaching works.”